Środki językowo-obrazowe służące etykietowaniu polityków w memach internetowych - Niekrewicz, Agnieszka Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
This article presents techniques for creating a negative image of a party and their representatives in Internet memes. The author indicates the typical for memes linguistic measures used for depreciation of individual politicians and at the same time contributing to the perpetuation of their axiologically unequivocal image, usually based on a single exaggerated feature. The author analyses examples of repetitions of lapses committed by politicians, key words that characterize them according to memetic scheme, descriptive and evaluative names replacing the names, verbal jokes based on polysemy and homonymy as well as spelling innovation.